Thyroid stimulating hormone resistance syndrome a case report - Ashrafuzzaman, SM; Latif, Zafar A (Ibrahim Medical College Journal, 2015)
Resistance to thyrotropin or thyroid stimulating hormone (RTSH) can be defined as decreased responsiveness to thyroid stimulating hormone (TSH) characterized by high TSH with normal but occasionally low T4 and T3 usually in absence of goiter or ectopic thyroid. It can be diagnosed when TSH is >30 mIU/L but free T4 (FT4) is within normal limit. Patient usually presents in euthyroid state with abnormally high TSH but may also present with mild to overt hypothyroidism. The precise prevalence is not known, but 20-30% infants may show transient mild RTSH. In adults it is rare. Here we report a case of RTSH in which a 19 years old young girl presented in euthyroid state with mild goiter. Ibrahim Med. Coll. J. 2014; 8(1): 32-33